(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Ayurveda consider Health and Disease both as the products of food and life style. Today when population is moving with modernization in the 21st century a lot of new diseases emerge out due to faulty life style, improper diet and unhealthy food lack of exercise, mental stress and sleep all are disturbs the biological clock of human being and produce many new life style diseases. Ajirna is the one of the most common disease which is originate from digestive insufficiency (Agni) due to all above factors of modern Era. Ayurveda is the ancient Indian system of medicine, deals with management and prevention of disease. Ayurveda has given prime importance to Agni as it is one of the basic biological elements of the living body. Its own physical characteristics, location and function and secretions like digestive juices and enzymes which participate in the digestive and metabolic functions. Therefore, Ayurveda considers Dehagni as the cause of life, Complexion, Strength, Health, Oja, Teja (energy) and Prana. Ayurveda consider that no disease ever be develop without the derangement of Agni. Ajirna arises as a result of less, excessive and irregular digestion of food and long term of this situation production of Amadosa and circulate all over the body. Further Amadosa combined with other Dosas and Dushyas vitiated them and produce many diseases. Preventive measures like Dincharya, Ratricharya, Ritucharya, Sadvrita and Pathya palana Dasvidhsbhojana Grahan Niyam are the preventive measure for Ajirn in Ayurveda.